IPM in Spanish Citrus: Current Status of Biological Control - Urbaneja, Alberto; Tena, Alejandro; Jaques, Josep A.; Monzó, César (2017)
Spain is the largest citrus producer within the European Union and the fifth worldwide with an average production of 5 million tons per season. Most of it is exported to third countries. Indeed, according to FAO, Spain is considered the first citrus exporter worldwide. Spanish citrus production is mainly destined to fresh market. Due to the high fruit quality standards demanded by this market, citrus pest management has to provide fruit with almost no pest presence or damage and at the same time, with minimal pesticide residues. International market demands place Spanish citrus industry in an unbeatable position to implement area-wide Integrate Pest Management (aw-IPM) programs. In the last years the citrus producing area that adopted IPM programs has dramatically increased. In 2012 more than 19% of the production already followed IPM regulations and that was a 5-fold increment relative to 2005. The current trend indicates that the number of growers adopting IPM systems will keep increasing over the coming years. The present article summarizes the current status of Spanish citrus IPM, how pests are hierarchized according to their biological control and which are the available IPM tools for growers. Large scale implementation of this management approach will permit Spanish citrus production to make a qualitative leap in a society that seeks for healthier eating habits and more environmental friendly production systems.